2021
DOI: 10.1002/er.7021
|View full text |Cite
|
Sign up to set email alerts
|

A neutronic investigation of tristructural isotropic‐duplex fuel in a high‐temperature reactor prismatic seed‐and‐blanket fuel block configuration with reduced power peaking

Abstract: Summary This paper presents the neutronic analysis of a tristructural isotropic (TRISO)‐duplex fuel loaded into the high‐temperature reactor (HTR) prismatic fuel block designs for a seed‐and‐blanket (S&B) reactor model. The selected fuel block design is the simplified model of a representative fuel configuration for the gas turbine–module helium reactor (GT‐MHR) and high‐temperature engineering test reactor (HTTR). The duplex fuel pellet comprises of UO2 as the seed and ThO2 as the blanket and uses the TRISO f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 66 publications
1
11
0
Order By: Relevance
“…Figure 11 depicts how the FTC becomes increasingly negative, which is advantageous, as the packing percentages of the TRISO fuels increase. The FTC range of the fuels with 40% packing fraction and 10 wt% 235 U/U is similar to that of the TRISO UO 2 fuel described in prior studies 10,14 . Using a higher uranium enrichment results in a weaker FTC value that is up to 20% and 24% less negative for the duplex and homogeneous fuel with a 40% packing fraction, respectively.…”
Section: Resultssupporting
confidence: 68%
See 4 more Smart Citations
“…Figure 11 depicts how the FTC becomes increasingly negative, which is advantageous, as the packing percentages of the TRISO fuels increase. The FTC range of the fuels with 40% packing fraction and 10 wt% 235 U/U is similar to that of the TRISO UO 2 fuel described in prior studies 10,14 . Using a higher uranium enrichment results in a weaker FTC value that is up to 20% and 24% less negative for the duplex and homogeneous fuel with a 40% packing fraction, respectively.…”
Section: Resultssupporting
confidence: 68%
“…Fuel mass distribution heterogeneity exists at the fuel rod level as well as between fuel rods in duplex fuel blocks. Although previous studies have demonstrated that its power distribution is more stable than that of an SBU fuel block configuration, it is not as flat as the homogeneous fuel block 14 . The pin power peaking for duplex and homogeneous fuel blocks with different packing values is shown in Figure 15.…”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations